2005
DOI: 10.1042/bj20050364
|View full text |Cite
|
Sign up to set email alerts
|

Carbohydrate-remodelled acid α-glucosidase with higher affinity for the cation-independent mannose 6-phosphate receptor demonstrates improved delivery to muscles of Pompe mice

Abstract: To enhance the delivery of rhGAA (recombinant GAA, where GAA stands for acid α-glucosidase) to the affected muscles in Pompe disease, the carbohydrate moieties on the enzyme were remodelled to exhibit a high affinity ligand for the CI-MPR (cation-independent M6P receptor, where M6P stands for mannose 6-phosphate). This was achieved by chemically conjugating on to rhGAA, a synthetic oligosaccharide ligand bearing M6P residues in the optimal configuration for binding the receptor. The carbonyl chemistry used res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
97
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 102 publications
(100 citation statements)
references
References 59 publications
3
97
0
Order By: Relevance
“…This is particularly likely in the case of HP-GAA in which higher levels of exposed mannose may result in unproductive targeting of the enzyme to endothelial cells via the mannose receptor. Of note, recent studies demonstrated that chemically attaching synthetic bis-M6P containing glycans to oxidized sialic acid residues of CHO-GAA (neo-rhGAA) resulted in improved glycogen reduction from the skeletal muscles of GAA knockout mice [30,31]. Since neo-rhGAA contains significantly less exposed mannose residues as compared to HP-GAA, these data demonstrate that if non-productive targets can be avoided, the concept of further exploiting uptake via the cation independent M6P receptor may offer a path to an improved therapeutic.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is particularly likely in the case of HP-GAA in which higher levels of exposed mannose may result in unproductive targeting of the enzyme to endothelial cells via the mannose receptor. Of note, recent studies demonstrated that chemically attaching synthetic bis-M6P containing glycans to oxidized sialic acid residues of CHO-GAA (neo-rhGAA) resulted in improved glycogen reduction from the skeletal muscles of GAA knockout mice [30,31]. Since neo-rhGAA contains significantly less exposed mannose residues as compared to HP-GAA, these data demonstrate that if non-productive targets can be avoided, the concept of further exploiting uptake via the cation independent M6P receptor may offer a path to an improved therapeutic.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to CHO-GAA, these included rhGAA produced in milk of transgenic rabbits (tgGAA) and a carbohydrate engineered form of rhGAA containing high levels of M6P (HP-GAA) also produced in CHO cells. The HP-GAA, prepared by enzymatic addition of M6P to mannose residues, was of particular interest because effective targeting of GAA to the lysosomal compartment of cardiac and skeletal muscle depends upon M6P receptor mediated uptake [29][30][31].…”
Section: Discussionmentioning
confidence: 99%
“…25,45,46 Until now, the reason why the skeletal muscle is more refractory than the heart to enzyme therapy is unclear, but may be related to the larger mass of skeletal tissue, and perhaps also to the differences in the relative accessibility of the circulating enzyme to different tissues. 47 The skeletal muscles also purportedly have less cation-independent M6P receptor that is essential for cellular uptake of the lysosomal enzyme. 47 West et al, 48 taking advantage of the immature immune response of newborns who do not yet produce antibodies to T-cell-independent antigens including the major blood-group antigens, reported successful cardiac transplantation in ABO-incompatible infants aged between 4 h and 14 months.…”
Section: Neonatal Lentivirus Gene Transfer For Murine Gsdii So Kyosenmentioning
confidence: 99%
“…47 The skeletal muscles also purportedly have less cation-independent M6P receptor that is essential for cellular uptake of the lysosomal enzyme. 47 West et al, 48 taking advantage of the immature immune response of newborns who do not yet produce antibodies to T-cell-independent antigens including the major blood-group antigens, reported successful cardiac transplantation in ABO-incompatible infants aged between 4 h and 14 months. Of all the 10 infants studied, the overall survival was 80%, and in only 1 infant was a mild humoral rejection noted in the autopsy.…”
Section: Neonatal Lentivirus Gene Transfer For Murine Gsdii So Kyosenmentioning
confidence: 99%
“…Based on these observations, efforts were made to improve the delivery of the therapeutic enzyme to affected tissues by increasing its affinity for the CI-MPR. Enzymatic adjunction of oligosaccharides to GAA using N-acetylglucosamine-1-phosphotransferase and N-acetylglucosamine-1-phosphodiester-a-N-acetylglucosaminidase was tested (66). This hypermannose-6-phosphorylated enzyme (HP-GAA) was no more effective at clearing glycogen from Pompe mice than the unmodified enzyme, due to a sequestration by mannose receptors on endothelial cells and macrophages (66).…”
Section: Enzyme Modification and Enhanced Deliverymentioning
confidence: 99%